Challenging the European southern refugium hypothesis: Species‐specific structures versus general patterns of genetic diversity and differentiation among small mammals. Issue 2 (17th December 2018) - Pedreschi, Debbi; García‐Rodríguez, Oxala; Yannic, Glenn; Cantarello, Elena; Diaz, Anita; Golicher, Duncan; Korstjens, Amanda H.; Heckel, Gerald; Searle, Jeremy B.; Gillingham, Phillipa; Hardouin, Emilie A.; Stewart, John R.
Abstract: Aim: In this study, we conduct a quantitative meta‐analysis to investigate broad patterns of genetic variation throughout large geographical regions in order to elucidate concordant geographical patterns across species and identify common historical processes to better inform the "cryptic refugia" versus the traditional "southern refugia" hypothesis debate. Location: Europe. Time period: Late Pleistocene to present day. Major taxa studied: Small mammals (Rodentia, Eulipotyphla). Methods: A meta‐analysis was performed on large‐scale patterns of genetic diversity for 19 species from 59 papers. For each species, haplotype and nucleotide diversity were calculated using the mitochondrial D‐loop and compared to the species' range. Results: No consistent patterns were observed between mitochondrial DNA (mtDNA) diversity indices (nucleotide and haplotype diversity) and any of the indicators of distribution examined [latitude and longitude (max, min, centre, range)]. The patterns of genetic diversity observed in all the 19 species studied appear to be species‐specific. Main conclusions: In contrast to the traditional southern refugial hypotheses, we found no evidence for a consistent south–north post‐glacial expansion. Instead individual species appear to respond to climate oscillations in niche‐specific ways. This individual nature of each species' phylogeographical history indicates a complex web of post‐glacial recolonization dynamics across Europe.